Our global neighbourhood : report... (O.U.P. OxfordGB, 1995)
Deals with how the world has been transformed since 1945, making changes necessary in our governance arangements. Makes recommendations for promoting security in its widest sense; managing economic interdependence; and for reforming the United Nations in ways that also offer a larger role to people through the organizations of international civil society. Addresses the need for extending on the global stage the rule of law. Draws attention to the world's need for enlightened leadership.
DC